Minipuberty of human infancy – A window of opportunity to evaluate hypogonadism and differences of sex development? - Renault, Christoffer Højrup (Ann Pediatr Endocrinol Metab, 2020)
Activation of the hypothalamic-pituitary-gonadal (HPG) axis happens in 3 phases during life. The first phase is during fetal life and is only separated from the second phase, called minipuberty, by the high concentration of placental hormones at birth. The third period of activation of the HPG axis is puberty and is well-described. Minipuberty consists of the neonatal activation of the HPG axis, mainly in the first 1–6 months, where the resulting high levels of gonadotropins and sex steroids induce the maturation of sexual organs in both sexes. With gonadal activation, testosterone levels rise in boys with peak levels after 1–3 months, which results in penile and testicular growth. In girls, gonadal activation leads to follicular maturation and a fluctuating increase in estrogen levels, with more controversy regarding the actual influence on the target tissue. The regulation of the HPG axis is complex, involving many biological and environmental factors. Only a few of these have known effects. Many details of this complex interaction of factors remain to be elucidated in order to understand the mechanisms underlying the first postnatal activation of the HPG axis as well as mechanisms shutting down the HPG axis, resulting in the hormonal quiescence observed between minipuberty and puberty. Minipuberty allows for the maturation of sexual organs and forms a platform for future fertility, but the long-term significance is still not absolutely clear. However, it provides a window of opportunity in the early detection of differences of sexual development, offering the possibility of initiating early medical treatment in some cases.